Induction of Pyroptosis and Its Implications in Cancer Management - Wang, Yan-Yang; Liu, Xin-Lan; Zhao, Ren (Frontiers in Oncology, 2019)
Pyroptosis is a gasdermins mediated programmed cell death, which has been widely studied in inflammatory disease models. Recently, there are growing evidences that pyroptosis can be chemically induced in cancer cells without any bacterial or viral infection. Pyroptosis may affect all stages of carcinogenesis and has become a new topic in cancer research. In this review, we first briefly introduced pyroptosis. In the subsequent section, we discussed the induction of pyroptosis in cancer and its potential role as a promising target for cancer therapy. In addition, the biological characteristics of gasdermin D (GSDMD) and gasdermin E (GSDME), two important pyroptosis substrates, and their prognostic role in cancer management were reviewed. These results help us to understand the pathogenesis of cancer and develop new drugs, which based on pyroptosis modulation, for cancer patients.